Environmentally Friendly Extraction of Bioactive Compounds from Spruce and Pine Needles to Obtain Extracts with Antioxidant and Antimicrobial Activity - Mezulis Marcis; Arbidans Lauris; Nikolajeva Vizma; Lauberts Maris; Grinfelds Uldis; Klavins Maris (Environmental and Climate Technologies, 2025)
Timber harvesting of coniferous trees (the most abundant species in the Northern Hemisphere) leaves significant greenery side streams – coniferous needles and branches (pine, spruce and other species). Coniferous needles have been widely used in ethnomedicine, and recent research characterizes them as rich sources of biologically active compounds with immunostimulatory and anti-inflammation activities, as well as they are traditionally used to treat inflammation of the respiratory tract, colds and flu. However, new sustainable extraction methods should be proposed to obtain coniferous needle extracts with biomedical application potential. Classical extraction methods (stirring and heating) were used in this study and compared with ultrasonic treatment, and process duration and temperature optimisation were performed. During extraction, glycerol and propylene glycol, solvents widely used in the food and pharmaceutical industries, were used to improve the extracts’ stability. Obtained coniferous needle and branch extracts were characterized by their antiradical activities (17–82 % Trolox eq.) and total polyphenol concentration (6–22 % gallic acid eq.) was analysed. The extracts were tested for antibacterial and antifungal activity, which demonstrates activities comparable to synthetic drugs with potentially lower side effects caused by drugs.